2013
DOI: 10.1186/1471-2393-13-107
|View full text |Cite
|
Sign up to set email alerts
|

Increasing caesarean section rates among low-risk groups: a panel study classifying deliveries according to Robson at a university hospital in Tanzania

Abstract: BackgroundRising caesarean section (CS) rates have been observed worldwide in recent decades. This study sought to analyse trends in CS rates and outcomes among a variety of obstetric groups at a university hospital in a low-income country.MethodsWe conducted a hospital-based panel study at Muhimbili National Hospital, Dar es Salaam, Tanzania. All deliveries between 2000 and 2011 with gestational age ≥ 28 weeks were included in the study. The 12 years were divided into four periods: 2000 to 2002, 2003 to 2005,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
123
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(151 citation statements)
references
References 27 publications
21
123
1
6
Order By: Relevance
“…[1][2][3] Developed countries like the Unites States have seen a drastic rise in C-Sections from 1996 to-2011. 4 The developing world too has seen a similar rise.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Developed countries like the Unites States have seen a drastic rise in C-Sections from 1996 to-2011. 4 The developing world too has seen a similar rise.…”
Section: Introductionmentioning
confidence: 99%
“…Litorp et al [11] in Dar es Salaam-Tanzania also found that Groups 1, 3 and 5 are the largest contributors to the overall caesarean section rate in their university hospitals.…”
Section: K Achille Et Al Open Journal Of Obstetrics and Gynecologymentioning
confidence: 96%
“…However, our Caesarean section rates are between 35.2% and 52.1% reported by Farghali et al [10] respectively in two Cairo hospitals (academic and military) in Egypt in 2014. In Tanzania in 2013, Litorp et al [11] noted a dramatic increase in the caesarean section rate in a decade from 19% to 49%. The average caesarean rate in this university hospital was 46% during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…4 When it comes to such centres the C-Section rates have been found to be universally higher both in the developed and the developing worlds. [1][2][3][4] The reason could be due to differences in the cases that that they deal with depending upon their geographical location, the obstetric profile of the cases, social and logistical factors This would make it difficult to have a generalized or uniformly appropriate C-Section rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In 1985 WHO stated that a C-section rate of above 15% is not justifiable at the same time stressed that every effort be made to provide CSection when needed rather than aim for a particular rate. 6 It is very difficult at the level of an individual health care facility, particularly tertiary care centre to determine an appropriate rate of CS.…”
Section: Introductionmentioning
confidence: 99%